Re-thinking energy efficiency in European policy: Practitioners' use of 'multiple benefits' arguments. (10th February 2019) - Fawcett, Tina; Killip, Gavin
Abstract: There is increasing interest in the idea that energy efficiency has economic, environmental and social impacts beyond energy and cost saving - a 'multiple benefits' perspective. However, present EU-decision making on energy efficiency is based on assessment of a very narrow range of costs and benefits. This paper investigates whether and how advocates of energy efficiency have used multiple benefits to frame their interactions with policy-makers at EU and UK level, and to broaden the appeal of energy efficiency. Nine semi-structured interviews were conducted with key practitioners from industry-backed or trade organisations and environment-focussed NGOs. All respondents regularly made use of multiple benefits arguments. Their experience is that these arguments are most persuasive when linked to the values and priorities of decision-makers and politicians, most of whom do not value energy efficiency as a benefit in itself. Different contexts and different benefits are more or less salient for different stakeholders. This framing sets energy efficiency decisions in a broad economic, environmental and social context. As such it requires more evidence than a simple focus on energy savings, and different sorts of evidence which can connect with a variety of decision makers. The importance of recognising differing contexts, actors, values, priorities has led to the development of an alternative visualisation of multiple benefits, which de-centres energy efficiency. Highlights: 'Multiple benefits' identifies economic, social and environmental impacts of energy efficiency. Leading NGOs and trade associations use this framing to influence EU policy makers. Multiple benefits arguments work best linked to values and priorities of policy makers. Persuasive case studies as well as quantitative evidence are required. A new visualisation of multiple benefits has been developed, which 'de-centres' energy efficiency.